Prediction of groundwater contaminants from cattle farm using Visual MODFLOW - Ebrahim, Mohammad Nazri; Che Man, Hasfalina; Mohamed Zawawi, Mohamed Azwan; Hamzah, Muhammad Hazwan (Universiti Putra Malaysia Press, 2019)
Livestock operation activities such as cleaning operation, feeding, milking and manure disposal are potential sources of contaminants into nearby surface and groundwater. In this study, the number of wastes generated from a cattle farm in Ladang 16 UPM, Serdang Selangor was estimated. Two monitoring wells were constructed at the site for groundwater quality monitoring assessment. The concentration of pollutants such as Potassium, Nitrate, and Copper was used in the simulation as an initial waste state. The simulation was conducted using Visual MODFLOW Software to predict the contaminants in groundwater. The aim was to predict the concentration of the pollutants distributed in groundwater and surface water sources in 365 days. Results of MODFLOW simulation showed that the flow of groundwater was in the direction towards the pond. The concentrations of Potassium, Nitrate, and Copper were predicted to accumulate in the groundwater to the pond within a year but the values were still below the drinking water standard. The groundwater contaminants could be due to seepage from the manure storage basin through subsoil into the shallow aquifer.